PENGARUH BRAND IMAGE TERHADAP LOYALITAS PELANGGAN PADA KORAN HARIAN RIAU POS - Fitri Anggraini; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Brand image is the consumer perception of a brand consisting of a set of brand associations that exist in the minds of consumers, which connects the consumer thinking toward a brand. Perceptions formed by personal experience that consumers can become stronger if consumers experience the positive experience of the product. Customer loyalty is the customer who has a tendency to make repeat purchases of the products / services of the same company, has a high consistency in the company, and have immunity against other companies. This research was conducted at PT. Riau Pos Intermedia located on Jl. H. R. Soebrantas Km 10.5, Panam, Pekanbaru. Penelitian ini goal done to determine the effect of brand image on customer loyalty in Riau Pos daily newspaper. The method used In this research was descriptive and quantitative with SPSS program, where samples used is customer Riau Pos daily newspaper and as an information source is the HR and Finance Manager. To determine the sample using the formula Slovin, sampling with purposive sampling method. The technique of collecting data through interviews, observation, and questionnaires.The results of data analysis includestest validity, reliability, and simple linear regression, brand image in this research include the strength of brand association, brand association excellence, uniqueness of brand associations. Each one has an indicator interrelated and positive effect on customer loyalty in Riau Pos daily newspaper. It can be concluded, the value of t (11,420)> t table (1,989) and Sig. (0,000) <0.05. This means that the brand image significant effect of customer loyalty.Keyword: brand image, customer loyalty